Panhypopituatarism and Azoospermia - Shkembi E; Daniele N; Zinno F (Open Journal of Thyroid Research - Peertechz Publications, 2017)
The pituitary gland is a small gland attached to the lower part of the brain. The term hypopituitarism refers to a loss in the production of hormones by the pituitary gland, which produces a variety of different hormones: ACTH: ACTH is made in the pituitary gland and travels through the bloodstream to the adrenal glands. It stimulates the adrenals to release cortisol, a key factor in many functions in the body's metabolism of fats, carbohydrates, sodium, potassium, and protein as well as blood pressure. TSH: Controls the production of thyroid hormones by the thyroid gland. Follicle-forming hormone (FSH): LH and FSH control both fertility in both sexes as well as the production of sex hormones (estrogen and progesterone by the ovaries in women and testosterone by the testicles in men). Let's talk about the hormonal regulation of the male reproductive system. So hormones are part of the endocrine system, there are many hormones that act on the reproductive system that stimulate for a gamete production.